Business Games with Intelligent E-Learning Systems: A Fundamental Study - Alami, M. El; Arriaga, F. de (Current Aspects in Business, Economics and Finance Vol. 4, 2022)
The desire to make business games more pedagogically capable opens up the prospect of collaboration with current intelligent tutors or intelligent e-learning systems. Due to the laborious and challenging collaboration caused by the lack of specific standards, this subject has not yet been studied. The paper examines the likelihood of such cooperation, as well as the features of business games and intelligent tutors or e-learning systems that would enable and support such cooperation. The combination of a well-known business game with an existing intelligent e-learning system is specifically discussed, along with the modifications that have to be made in order for this cooperation to work. The efficiency of this collaboration is demonstrated by tests that have been conducted, their objective outcomes, and the opinions of the pupils. The integration of both, the BG and the IELS, is used as a learning aid for several graduate distance courses. Improvements have been introduced to obtain a better cooperation. The new results obtained show their beneficial effects.